Organ-specific gene expression in transgenic potato: the cloning a new promoter of a class I patatin gene - Yefimenko, I.M.; Medvedeva, T.V.; Kovalenko, P.G.; Gazaryan, K.G.; Galkin, A.P. (Биополимеры и клетка, 1995)
Using synthetic oligonucleotide probes homologous to conservative AT-rich motif of patatin genes class I of two different clones were isolated from a potato genomic library. One of two different genomic clones named λpat122 was subcloned and analysis 5'-region sequences. Using the chloramphenicol acetyltransferase (CAT) gene as a reporter it has been shown that a 1.8 kb promoter fragment of the class I patatin gene λpat122 provides all the information necessary for both tuber-specific and sucrose-induced expression in leaves in transgenic potato plants. З застосуванням синтетичних олігонуклеотидних зондів, гомологічних консервативному АТ-багатому мотиву пататинових генів классу I, з геномної бібліотеки генів картоплі виділено два клони. Один клон, названий λpat122 , було субклоновано і визначено нуклеотидну послідовність 5'-кінцевої ділянки. Використовуючи ген хлорамфеніколацетилтрансферази як репортерний, було показано, що 1.8 kb фрагмент промотора гена пататину λpat122 несе в собі всю інформацію, необхідну для бульбо-специфічної і цукрозо-регульованої експресії у трансгенних рослинах картоплі. С применением синтетических олигонуклеотидных зондов, гомологичных консервативном АО -богатом мотиве пататинових генов класса I, геномной библиотеки генов картофеля выделенs два клоны. Один клон, названный λpat122 , был субклонован и определена нуклеотиднаяпоследовательность 5' - концевого участка . Используя как репортерный ген хлорамфениколацетилтрансферази , было показано, что 1.8 kb фрагмент промотора гена пататину λpat122 несет в себе всю информацию, необходимую для клуюне-специфической и сахарозы регулируемой экспрессии в трансгенных растениях картофеля.